Analysis of biology laboratory profile: A case study in State Senior High School 1 of Rasau Jaya in Kubu Raya Regency - Wiwin Saraswati; Wolly Candramila; Asriah Nurdini Mardiyyaningsih (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The biology laboratory at State Senior High School (SSHS) 1 of Rasau Jaya has not been fully utilized, necessitating evaluation and improvement. This study aimed to determine the suitability of laboratory facilities and infrastructure at SSHS 1 of Rasau Jaya in relation to the existing standards set by the national regulations. This is a case-study research with a qualitative descriptive approach. The single respondent, namely the head of the biology laboratory at the respective school, provided insights into the seven analyzed aspects. Data collection was conducted through interviews and observations. The observations covered four aspects. Only the availability and preparation of laboratory equipment and materials met the standards of Permendiknas No. 24 of 2007. In the other six aspects, several indicators were still found to be non-compliant. The observation results supported this finding, as the four observed aspects have not yet fully met the expected standards. The low fulfillment of aspects in the laboratory profile at school requires further attention, particularly regarding the indicators that remain inadequate. A well-developed laboratory profile will support the optimal function and role of the laboratory.